The Warsaw Ghetto : historical map over a contemporary grid plan of Warsaw - Weszpiński, Paweł E.; Żydowski Instytut Historyczny im. Emanuela Ringelbluma (Emanuel Ringeblum Jewish Historical Institute, 2018)
Descriptions of points on the map -- Contemporary commemorations, monuments, orientation points